Utility of Semiquantitative Strain Elastography for Differentiation Between Benign and Malignant Solid Renal Masses - Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad; Bozgeyik, Zulkif; Onur, Ahmet Rahmi; Orhan, Irfan (Wiley, 2015)
Objectives-The aim of this study was to determine the role of semiquantitative strain elastography for differentiation of benign and malignant solid renal masses. Methods-Seventy-one patients with solid renal masses were prospectively examined with ultrasound elastography after grayscale sonography. Strain elastography was used to compare the stiffness of the renal masses and renal parenchyma. The ratio of strain in a renal mass and nearby renal parenchyma was defined as the strain index value. Mean strain index-values for benign masses (n = 29; 24 angiomyolipomas and 5 oncocytomas) and malignant masses (n = 42; 34 renal cell carcinomas, 4 transitional cell carcinomas, 3 metastases, and 1 lymphoma) and mean strain index values for angiomyolipomas and renal cell carcinomas were compared. Results-There were no significant differences in the mean age of the patients, mean diameter of the masses, and mean probe-mass distance between benign and malignant groups. The mean strain index value +/- SD for malignant masses (4.05 +/- 2.17) was significantly higher than the value for benign masses (1.43 +/- 0.94; P < .05). The mean strain index value for renal cell carcinomas (4.30 +/- 2.27) was significantly higher than the value for angiomyolipomas (1.28 +/- 1.01; P < .0001). Conclusions-Strain elastography maybe a useful imaging technique for differentiation between benign and malignant solid renal masses.
Keywords: genitourinary ultrasound; renal mass; strain elastography; strain index value